Subtitusi Gula Tebu Dan Gula Aren Dalam Pembuatan Tepache Buah Naga Dengan Penambahan Whey - Evang Jelin Istiana Salombe; Natal Olotua Sipayung; Tito Pratama; Dailami . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Fermented beverages are rapidly developing because they are considered to provide benefits for digestive health and are part of the functional food trend. One of the fermented beverage innovations that has the potential to be developed based on local ingredients is dragon fruit Tepache with the addition of whey. This study aims to determine the effect of using two types of sugar, namely cane sugar and palm sugar, on the sensory characteristics of Tepache made from dragon fruit flesh and skin with the addition of whey. The study used an experimental method with a completely randomized design with one factor and two levels and involved 30 panelists consisting of trained, semi-trained, and untrained panelists. Assessment was carried out through organoleptic tests on four quality parameters, namely color, aroma, texture, and taste, and analyzed using the Mann-Whitney U test. The results showed that cane sugar provided a brighter color and was preferred by panelists, while aroma and texture showed no significant differences in most panelists. The taste of Tepache from both treatments remained acceptable to consumers. In conclusion, the use of cane sugar provided better visual characteristics, but both types of sugar were still suitable for use in making dragon fruit Tepache with the addition of whey as a functional fermented beverage.